SELECTIVITY OF PURIFIED EXTRACT FROM THE LEAVES OF Tithonia diversifolia (Hemsley) A.Gray AGAINST HELA CELLS - Wahyuningsih, M. Sri Hartati; Syarif, Rul Afiyah; Suharmi, Sri; Murini, Tri; Saputra, Firandi; W, Adiguno Suryo (Majalah Obat Tradisional, 2013)
Tithonia diversifolia (Hemsley) A.Gray is a kind of plant and traditionally used to cure various diseases. The previous research found that T.diversifolia had antiproliferation effect on colon cancer cell (Col2). Sample preparation using biossay guided extraction and partition method, could simplify the active compounds of the extract. Research on the selectivity of purified extract from the leaves of Tithonia diversifolia (Hemsley) A.Gray) against HeLa cells hasnât been known yet. The aim of this research was to find out the selectivity of purified extract of T.diversifoliaâs leaves on HeLa cell compared to vero cell and to find out the Fifty Percent Inhibition Concentration (IC50), and its selectivity index. Extraction of T. diversifoliaâs leaves were done by maceration method using chloroform and methanol. Both of extract were tested by MTT cytotoxic assay on HeLa cells in vitro with serial doses (0,24 - 500Î¼g/mL). Each group was replicated 3 times. The absorbance was read using ELISA at Î» 540nm. IC50 was analyzed by probit regression on SPSS 15 for Windows. Partition (purified extract) of the active extract was done using Petroleum eter (PE), and tested by MTT cytotoxic assay on HeLa cells in vitro. Â The IC50 methanol extract to HeLa cell in vitro is 1006,99Î¼g/mL, IC50 chloroform extract is 16,61Î¼g/mL. Â The IC50 of soluble PE is 325,33Î¼g/mL. Â and IC50 of insoluble PE is 3,078Î¼g/mL. The IC50 value of insoluble PE to Vero cell is 80,30 Î¼g/mL. Selectivity index of purified extract (PE insoluble extract) is 26.09.Â